Measuring satisfaction of mustahik services Dompet Dhuafa using customer service index and importance-performace analysis - Wibowo, Prasetyo; -, S.Kom; -, Agung Nugroho; A. S.Sos, M. Noor Awaluddin; -, M. Kesos (2023)
Excellent service to both muzaki and mustahik for zakat management organizations is one of the advantages that must continue to be maintained and improve its quality. This research used the Customer Satisfaction Index (CSI) method to obtain importance and satisfaction values for each program service provided so that it can identify problems and recommend appropriate improvements. This research was used to determine the level of interest and satisfaction of beneficiaries from The Community Service Institution (LPM) Dompet Dhuafa mustahik service program in the form of a satisfaction index, as well as to find out priority aspects for improving the LPM Dompet Dhuafa mustahik service. The sampling and data collection technique was carried out using convenience sampling along with questionnaires, interviews and document study. A total of 31 respondents in the Jabodetabek area filled out surveys both face-to-face and telephone. Meanwhile, data analysis was carried out using two methods, namely the Customer Satisfaction Index and Importance-Performance Analysis (IPA). The dimension of Service Quality (ServQual) analyzed is related to 5 aspects, namely Tangibles, Reliability, Responsiveness, Assurance and Empathy. Based on the Importance Performance Analysis (IPA) analysis of mustahik services, in quadrant 1 there are 5 items that are the main priority for improvement. The satisfaction score of the LPM Dompet Dhuafa mustahik service program index is 78.60. The LPM Dompet Dhuafa mustahik service program is a part of the Mustahik Journey which serves mustahik segments with emergency criteria and open disbursement proportionally and continues to upgrade the quality of its services. This research has limited respondents and time in exploring the mustahik segmentation and area. This research can be a reference for further research related to the mustahik service program, mustahik journey and zakat disbursement. This research shows that that the role of LPM DD is very important in the mustahik journey and it is necessary to continue to improve service quality and listen to the aspirations of various parties.